Baseline microbiota of blueberries, soil, and irrigation water from blueberry farms located in three geographical regions - Angelica Abdallah-Ruiz; Clara Esteban-Perez; Shecoya B. White; Wes Schilling; Xue Zhang; Eric T. Stafne; Alejandro Rodríguez-Magaña; Fernando Peña-Baracaldo; Carlos A. Moreno-Ortiz; Juan L. Silva (Heliyon)
Bacterial microbiota was determined in fruit, soil, and irrigation water from blueberry (Vaccinium spp.) farms located in Cundinamarca, Colombia; Mississippi, United States; and Jalisco, Mexico. Bacterial communities were studied using 16S ribosomal ribonucleic acid (rRNA) gene amplification by targeting the V3–V4 hypervariable region. The most abundant phylum in fruit was Proteobacteria in Colombia and the United States and Firmicutes in Mexico. The most abundant phylum in soil and water was Proteobacteria for all regions. The top three genera found in fruit were Heliorestis (9.2 %), Rhodanobacter (3.3 %), and Sphingomonas (2.8 %) for Colombia, Heliorestis (23.1 %), Thiomonas (8.5 %), and Methylobacterium (3.3 %) for the United States, and Heliorestis (47.4 %), Thiomonas (9.1 %), and Bacillus (4.6 %) for Mexico. Colombia reported the highest (Padj < 0.05) alpha diversity for blueberries, and United States and Mexico had similar (Padj > 0.05) results. Beta diversity revealed bacterial communities in fruit differed (P < 0.05) by region. Bacterial differences existed between Colombia, United States, and Mexico for soil and fruit (P = 0.021, 0.003, and 0.006, respectively) and water and fruit (P = 0.003, 0.003, and 0.033, respectively). Blueberries grown in the three different regions have unique microbiota. Fruit and fruit-environment microbial composition also differed by region. These results provide a more complete profile of the bacterial communities on blueberries and their agricultural environments and could contribute to better management and decision-making practices in terms of plant health, food quality, and food safety.